A biocompatible macromolecular two-photon initiator based on hyaluronan. Issue 2 (29th November 2016) - Tromayer, Maximilian; Gruber, Peter; Markovic, Marica; Rosspeintner, Arnulf; Vauthey, Eric; Redl, Heinz; Ovsianikov, Aleksandr; Liska, Robert
Abstract : Binding a two-photon-initiator to hyaluronan hinders trans-membrane migration into cells and reduces cyto- and phototoxicity, enhancing biocompatibility. Abstract : The possibility of the direct encapsulation of living cells via two-photon induced photopolymerization enables the microfabrication of hydrogel scaffolds with high initial cell loadings and intimate matrix–cell contact. While highly efficient water-soluble two-photon initiators based on benzylidene ketone dyes have been developed, they exhibit considerable cyto- and phototoxicity. To address the problem of photoinitiator migration from the extracellular matrix into the cytosol, a two-photon initiator bound to a polymeric hyaluronan backbone (HAPI ) was synthesized in this work.HAPI exhibited a distinct improvement of cytocompatibility compared to a reference two-photon initiator. Basic photophysical investigations were performed to characterize the absorption and fluorescence behavior ofHAPI . Laser scanning microscopy was used to visualize and confirm the hindered transmembrane migration behavior ofHAPI . The performance ofHAPI was tested in two-photon polymerization at exceedingly high printing speeds of 100 mm s −1 producing gelatin-based complex 3D hydrogel scaffolds with a water content of 85%. The photodamage of the structuring process was low and viable MC3T3 cells embedded in the gel were monitored for several days after structuring.